Study of Water Quality as Seen from The Diversity of Phytoplankton in Situ Sipatahunan, Baleendah, West Java - Ita Fitriyyah; Rahmat Taufiq Mustahiq Akbar; Rifqoh Azkiya; Haikal Azmi (Biodidaktika : Jurnal Biologi dan Pembelajarannya, 2026)
Situ Sipatahunan serves as a source of irrigation, a tourist attraction, and a provider of domestic drinking water, making it important to the community of Baleendah. Monitoring water quality is necessary to detect potential pollution and ensure its suitability in supporting these functions. Phytoplankton is used as a bioindicator because it is sensitive to environmental changes. This study aims to assess the water quality of Situ Sipatahunan based on the phytoplankton community and its relationship with the physical and chemical parameters of the water. Sampling was carried out at three stations using purposive sampling based on different environmental conditions, using a 400 µm plankton net. 25. Data analysis used abundance, diversity, evenness, dominance, saprobic indices, and correlation tests. The results showed that there were 44 phytoplankton species in the waters of Situ Sipatahunan, consisting of the classes Bacillariophyceae, Chlorophyceae, Cyanophyceae, Dinophyceae, Xanthophyceae, Euglenophyceae, and Rhodophyceae. Abundance ranged from 855 to 1096 cells/L/L. Diversity levels were moderate (1.79–1.94), evenness was moderate (0.60–0.69), and dominance was low (0.22–0.29). There is a significant relationship between nitrate and phosphate levels and the level of phytoplankton diversity. Water quality is classified as β–Meso/oligosaprobic or lightly polluted.